2021
DOI: 10.9734/jpri/2021/v33i47b33149
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Knowledge, Attitude and Practice Regarding Gestational Diabetes Mellitus (GDM) and Its Control with Medical Nutritional Therapy among Antenatal Patients in a Tertiary Care Hospital in a Semi Urban Area

Abstract: Introduction: Gestational diabetes mellitus is a condition in pregnancy which can cause foetal and maternal complications. After delivery the newborn may have life threatening metabolic complications and later in life may suffer from obesity, glucose intolerance and Diabetes in early adulthood. The mother might also be at the risk of developing type-2 diabetes mellitus. So, the knowledge among the antenatal women will result in disease prevention and early detection. Aim and Objective: The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…(11) In 2021, another crosssectional study conducted in a tertiary hospital in Tamil Nadu showed more than half of the pregnant women accepted universal GDM screening; subjects reported acquiring knowledge from friends, medical professionals, family, and neighbors. (20) Post the launch of competency-based curricula for Indian medical undergraduates (IMUGs) in 2018 (13), the NMC visualized that the IMUGs would be able to provide holistic care to their patients by enunciating the competencies learned during their training program. While the initiative was revolutionizing in integrating different disciplines both horizontally and vertically, the focus was primarily on improvising teaching-learning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…(11) In 2021, another crosssectional study conducted in a tertiary hospital in Tamil Nadu showed more than half of the pregnant women accepted universal GDM screening; subjects reported acquiring knowledge from friends, medical professionals, family, and neighbors. (20) Post the launch of competency-based curricula for Indian medical undergraduates (IMUGs) in 2018 (13), the NMC visualized that the IMUGs would be able to provide holistic care to their patients by enunciating the competencies learned during their training program. While the initiative was revolutionizing in integrating different disciplines both horizontally and vertically, the focus was primarily on improvising teaching-learning strategies.…”
Section: Discussionmentioning
confidence: 99%